The sea wall - Marder, Marc 1955-; Duras, Marguerite 1914-1996 (Axiom Films, 2008)
Mrs. Dufresne is the matriarch of a small land-owning family who try to survive by working on rice fields located dangerously close to the ocean. Driven to fight against both nature and corrupt bureaucrats, she devises an imaginative scheme to build a dam against the sea with the help of the villagers - Container
Orig: Frankreich, 2007. - Based on the novel by Marguerite Duras. - "Suitable only for persons of 12 years and over" -- container. - Includes special features : Interviews for Cinémoi, the French Movie Channel, with director Rithy Panh and actress Isabelle Huppert ; Stills Gallery ; Trailer
original music, Marc Marder. Producers, Cati Couteau, Catherine Dussart ; director, Rithy Pahn ; writers, Michel Fessler, Rithy Panh ; cinematography, Pierre Milon ; film editing, Marie-Christine Rougerie ; music, Marc Marder
Keywords: Geschichte 1931; Rice farmers / Indochina / Drama; Women rice workers / Drama; Earth dams / Construction / Drama; Sea-walls / Indochina / Drama; Feature films; Foreign films; Kolonie; Landwirtschaft; Familie; Indochina / Drama; France / Colonies / Asia / Drama; Asien; Frankreich; Indochina; DVD-Video